2004
DOI: 10.1126/science.1094247
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Vectors in the Culex pipiens Complex

Abstract: In the Old World, some mosquitoes in the Culex pipiens complex are excellent enzootic vectors of West Nile virus, circulating the virus among birds, whereas others bite mainly humans and other mammals. Here we show that, in northern Europe, such forms differing in behavior and physiology have unique microsatellite fingerprints with no evidence of gene flow between them, as would be expected from distinct species. In the United States, however, hybrids between these forms are ubiquitous. Such hybrids between hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
440
2
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(478 citation statements)
references
References 21 publications
22
440
2
14
Order By: Relevance
“…p. pipiens. Alternatively, microsatellite data generated by Fonseca et al (2004) supports a hypothesis that Cx. p. pipiens and Cx.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…p. pipiens. Alternatively, microsatellite data generated by Fonseca et al (2004) supports a hypothesis that Cx. p. pipiens and Cx.…”
mentioning
confidence: 86%
“…pipiens f. molestus by using infrared spectrometry. Recently Fonseca et al (2004) reported unique microsatellite signatures among worldwide populations of Cx. p. pipiens and Cx.…”
mentioning
confidence: 99%
“…ND4 sequences from Culex restuans (Baltimore Co., MD) and Culex tarsalis (Kern Co., CA) were obtained as out group taxa and deposited in GenBank under accession numbers AY788866-AY788867. Primer sequences and PCR conditions were as stated by Gorrochotegui-Escalante et al (2000). Amplified fragments were separated, purified and sequenced as described above.…”
Section: (D) Mosquito Mitochondrial Variability (I) Pcr and Sequencingmentioning
confidence: 99%
“…Both subspecies have a global distribution and complicated population structure. For example, in North America and Asia extensive gene flow occurs between subspecies (Tabachnick & Powell 1983;Urbanelli et al 1997;Fonseca et al 2004), whereas in some parts of Africa gene flow between subspecies is partial (Urbanelli et al 1985(Urbanelli et al , 1995 or restricted ( Jupp 1978;Cornel et al 2003). Depending on location, members of this complex can be important vectors of nematodes that cause lymphatic filariasis and arboviruses such as St Louis encephalitis, West Nile and Rift Valley fever viruses (Hoogstraal et al 1979;Krida et al 1998;Day 2001;Nasci et al 2001;Fonseca et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation